Karipapdaging.com / Dwina Roslan - Roslan, Dwina (2021)
Food and Beverages Industry includes restaurants, cafeterias, cafes, fast-food joints, pubs, delis, food manufacturing operations, catering businesses, food transportation services and more. Work in this industry can range from packaging to preparing, transporting, and serving food or beverages. Food and Beverage is the most important industry at this moment after all disaster happened like Covid-19 and floods. This is because people need it even when they think they don’t want it which lead to constant growth. Every business we made will surely get profit, it’s either big or small but most important is we try and the product meets the demand. Looking back to every big company like Starbuck and Mc Donald, they also start from below but for sure it took a lot of courage and patient before they managed to go this big and well known all over the world. For our business, we are trying to convey food that has been subjected to rapid freezing and is kept frozen until used. Our product is preserved under low temperature and used over a long period. As for our packaging, we used a ready-to-go and bakery. This include a lot of process such as production, heating under a low temperature, keep it cool under a room temperature, packing and lastly let it freeze in the frozen. We choose curry puff as our product even though we know the process of making it is not as easy as you think because it is a kind of bakery and may not be able to last long. However, we choose to take risks as we are aware of our own abilities and have high confidence to continue this business. We bought a Styrofoam cooler to place our product every time we go for delivery to avoid the goods from melting. We are trying the best to make this happen. We rent a place for us to do all production so it will be easier for us to move.